OPERASIONAL PROSEDUR RESERVASI TIKET DI PT. OKE WISATA MANDIRI TOUR AND TRAVEL PEKANBARU - Anita Sopia Sari; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study was conducted to clarify the Operational Procedures Reserve Tickets at PT. Okay Independent Tour And Travel Tourism Pekanbaru. As for the background of this research is a form of service performed by PT. Oke Wisata Mandiri Tour And Travel Pekanbaru is not well in customer service. This research uses theory that discusses Agus Rianto Code Management Reserve to explain the phenomena found in the field. This study used qualitative methods, while the technique of data collection using interviews, observation and discussion with sources of research. Furthermore, the data in the form of data qualitative and quantitative data were analyzed with descriptive technical data analysis. Results of this study showed a difference error itinerary that consumers want to bokingang that was created by the reservations clerk. Mistakes in pingisian tickets include mistakes filling date, month, route the customer wants at the time of reservation. Plus the lack of SOP (Standard Operating Procedure) reservation that applied by PT. Oke Wisata Mandiri Tour And Travel, so Human Resources which are owned to serve consumers not optimal. So many complain that reported by consumers for errors made by the reservations clerk. Keywords: Operations, Procedures, Reservations